Analisis Normatif terhadap Dampak Pukat Harimau bagi Kelestarian Lingkungan - SEPAREN; LESTARI, RIKA; FIRDAUS, EMILDA; SUDARSO, YOS (Riau Law Journal, 2025)
Large nets pulled on the seabed with the help of ships that function to catch fish in large quantities, but trawl nets hurt the sustainability of marine ecosystems, especially coral reefs. This study is a type of normative research. Data were obtained from laws and regulations and literature related to the object of research. The data obtained were analyzed using qualitative descriptive methods. The results of the study showed that Law No. 45 of 2009 concerning Fisheries has normatively prohibited the use of trawls; sanctions for fishermen who use trawls can be in the form of administrative sanctions, criminal sanctions, and fines. Likewise, the Regulation of the Minister of Marine Affairs and Fisheries Number 2 / PERMEN-KP / 2015 regulates the subject of the prohibition of the use of trawls because of the many losses caused by the use of trawls (trawl nets), namely damage to coral reefs, non-selective fishing, affecting fish populations, disruption of marine ecosystem habitats, increasing marine pollution, and shrinking marine natural resources. So, it is necessary to pay attention to ethical norms and the principle of legal justice in utilizing resources, especially fish, so as not to damage the marine ecosystem.